Circular economy mapping in the palm oil value chain: Towards a conceptual framework for sustainable transition - Ali Sunandar; Fitri Andriyanti; Saipol Bari Abd Karim; Umi Kalsum Zolkafli (Jurnal Bisnis Kehutanan dan Lingkungan, 2026)
Background: The palm oil sector has long been a major contributor to Indonesia’s economy; however, it continues to face criticism for its environmental impact. The circular economy (CE) offers a transformative approach to shift the sector from a linear system to a regenerative model centered on resource recovery, waste reduction, and value retention. This study aims to systematically map CE opportunities across all phases of the palm oil value chain, including pre-production, cultivation, processing, and consumption, and to develop a conceptual framework that supports Indonesia’s transition to sustainability. Methods: A systematic literature review was conducted using the Scopus and Web of Science databases, following the PRISMA protocol. Publications from 2017 to 2025 were analyzed thematically to identify CE opportunities, key drivers, barriers, and interconnections across the value chain. Findings: CE opportunities were identified in every phase of the palm oil value chain. However, integration across phases remains limited, and coordination among stakeholders and institutions has yet to become systemic or well aligned. Conclusion: A holistic conceptual framework that links CE opportunities across all stages of the value chain is essential to enable a sustainable transition in Indonesia’s palm oil industry. Novelty/Originality of this article: This study presents the first comprehensive and phase-based mapping of CE practices in the palm oil sector and introduces an integrative conceptual framework that consolidates fragmented efforts into a coherent model for Indonesia’s sustainable circular transition.